2020
DOI: 10.1016/s2214-109x(19)30545-5
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of respiratory infections associated with seasonal influenza in children under 5 years in 2018: a systematic review and modelling study

Abstract: Background Seasonal influenza virus is a common cause of acute lower respiratory infection (ALRI) in young children. In 2008, we estimated that 20 million influenza-virus-associated ALRI and 1 million influenza-virus-associated severe ALRI occurred in children under 5 years globally. Despite this substantial burden, only a few low-income and middleincome countries have adopted routine influenza vaccination policies for children and, where present, these have achieved only low or unknown levels of vaccine uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
206
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(239 citation statements)
references
References 38 publications
8
206
1
3
Order By: Relevance
“…Like influenza and severe acute respiratory syndromes (SARS), environmental factors play a role for their spread and transmission Wong et al 2010). It is confirmed that influenza is a seasonal-depended respiratory disease, causing great health problems among human every year, particularly during winter and early spring (Huang et al 2017;Wang et al 2020). COVID-19 was also first confirmed in winter with low temperature and low humidity, which along with small diurnal temperature range were assessed to be the most important environmental factors favoring its transmission ( W a n g e t a l .…”
Section: Introductionmentioning
confidence: 99%
“…Like influenza and severe acute respiratory syndromes (SARS), environmental factors play a role for their spread and transmission Wong et al 2010). It is confirmed that influenza is a seasonal-depended respiratory disease, causing great health problems among human every year, particularly during winter and early spring (Huang et al 2017;Wang et al 2020). COVID-19 was also first confirmed in winter with low temperature and low humidity, which along with small diurnal temperature range were assessed to be the most important environmental factors favoring its transmission ( W a n g e t a l .…”
Section: Introductionmentioning
confidence: 99%
“…Excess mortality calculations have been done globally for seasonal influenza, arriving at 300 000-600 000 influenza-associated deaths occurring annually (Iuliano et al, 2018). While the majority of influenza mortality applies to elderly people, the death rate is also substantial for children at an estimated 34 000 deaths in 2018 (Wang et al, 2020). In comparison, the global death toll of COVID-19 is now 315 0 000 (status May 18).…”
Section: Excess Mortalitymentioning
confidence: 99%
“…It has a unique ability to cause a recurrence epidemic and pandemics in individuals of all ages. In growing children, it causes acute lower respiratory infections such as bronchitis and pneumonia [ 1 ]. The proportion of hospitalizations for children can reflect the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%